INERTIAL TECHNOLOGIES IN SYSTEMS FOR STABILIZATION OF GROUND VEHICLES EQUIPMENT - Sushchenko, Olha (Proceedings of National Aviation University (archive), 2016)
Purpose: The vibratory inertial technology is a recent modern inertial technology. It represents the most perspective approach to design of inertial sensors, which can be used in stabilization and tracking systems operated on vehicles of the wide class. The purpose of the research is to consider advantages of this technology in comparison with laser and fiber-optic ones. Operation of the inertial sensors on the ground vehicles requires some improvement of the Coriolis vibratory gyroscope with the goal to simplify information processing, increase reliability, and compensate bias. Methods: Improvement of the Coriolis vibratory gyroscope includes introducing of the phase detector and additional excitation unit. The possibility to use the improved Coriolis vibratory gyroscope in the stabilization systems operated on the ground vehicles is shown by means of analysis of gyroscope output signal. To prove efficiency of the Coriolis vibratory gyroscope in stabilization system the simulation technique is used. Results: The scheme of the improved Coriolis vibratory gyroscope including the phase detector and additional excitation unit is developed and analyzed. The way to compensate bias is determined. Simulation of the stabilization system with the improved Coriolis vibratory gyroscope is carried out. Expressions for the output signals of the improved Coriolis vibratory gyroscope are derived. The error of the output signal is estimated and the possibility to use the modified Coriolis vibratory gyroscope in stabilization systems is proved. The results of stabilization system simulation are given. Their analysis is carried out. Conclusions: The represented results prove efficiency of the proposed technical decisions. They can be useful for design of stabilization platform with instrumental equipment operated on moving vehicles of the wide class.